Comparative secretomics reveals novel virulence-associated factors of Vibrio parahaemolyticus - He, Yu; Wang, Hua; Chen, Lanming (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is a causative agent of serious human seafood-borne gastroenteritis disease and even death. In this study, for the first time, we obtained the secretomic profiles of seven V. parahaemolyticus strains of clinical and food origins. The strains exhibited various toxic genotypes and phenotypes of antimicrobial susceptibility and heavy metal resistance, five of which were isolated from aquatic products in Shanghai, China. Fourteen common extracellular proteins were identified from the distinct secretomic profiles using the two-dimensional gel electrophoresis (2-DE) and liquid chromatography tandem mass spectrometry (LC-MS/MS) techniques. Of these, half were involved in protein synthesis and sugar transport of V. parahaemolyticus. Strikingly, six identified proteins were virulence-associated factors involved in the pathogenicity of some other pathogenic bacteria, including the translation elongation factor EF-Tu, pyridoxine 5'-phosphate synthase, σ54 modulation protein, dihydrolipoyl dehydrogenase, transaldolase, and phosphoglycerate kinase. In addition, comparative secretomics also revealed several extracellular proteins that have not been described in any bacteria, such as the ribosome-recycling factor, translation elongation factor EF-Ts, phosphocarrier protein HPr and maltose-binding protein MalE. The results in this study will facilitate the better understanding of the pathogenesis of V. parahaemolyticus and provide data in support of novel vaccine candidates against the leading seafood-borne pathogen worldwide.